On complementability of certain generalized hypercenters in Artinian modules - Kurdachenko, L. A.; Petrenko, B. V.; Subbotin, I. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We prove that, in an Artinian module, the upper FC-hypercenter over an infinite FC-hypercentral locally solvable group has a direct complement. Thus, we obtain a generalization of one of Zaitsev’s theorems and one of Duan’s theorems.